The New Second Generation in Switzerland: Youth of Turkish and Former Yugoslav Descent in Zurich and Basel - Fibbi, Rosita (Amsterdam University Press, 2015)
Using data from the Integration of the Second Generation in Europe survey, this timely study focuses on the second generation of immigrants from Turkey and former Yugoslavia in Switzerland. A common thread running through the various chapters is a comparison with previous research on Switzerland concerning the second generation of Italian and Spanish origin. The authors provide valuable insights into the current situation of the children of Turkish and Yugoslav immigrants while underlining the historical similarities and differences of their respective incorporation processes.